Implementasi Akad Rahn di Lembaga Keuangan Syariah - Mulyono (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Pegadaian Syariah utilizes rahn contracts as one of the products and contracts used by Islamic financial institutions in Indonesia in their operational activities. Nevertheless, fiqh analysis is carried out to avoid impermissible violations. This is because one of the basic principles of Usul Fiqh states that any transaction is permissible unless there is clear evidence that the transaction violates sharia law. In practical terms, the main aspects of the rahn contract, namely marhun, marhun bih, shighah, and "aqidaini", are in accordance with sharia theory. However, there are some things that need to be explained further to ensure correct implementation from a sharia point of view. The parties involved in the rahn contract, namely rahin and murtahin, use pawned goods, but it is not specified how the goods are used. There are various benefits of lien or ar-rahn regulation in transactions, one of which is to strengthen trust between.